2017
DOI: 10.1002/nop2.113
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study of stress and its sources among health professional students at Makerere University, Uganda

Abstract: AimTo assess prevalence of stress and its sources among undergraduate health professional students at Makerere University.DesignThis was a descriptive cross‐sectional study using quantitative methods of data collection.MethodsThe study was conducted among 258 undergraduate health professional students (Medical, Dental and, Nursing students) at Makerere University. From each programme, students were recruited proportionately, while being selected conveniently from each year of study. Stress was measured using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…16 Research from Uganda shows the level of stress among health science students was 57.4% and a study from Zimbabwe reported a Higher prevalence of mental distress (64.5%) amongst first-year medical students. 16,17 In Somaliland at the University of Hargeisa, a lower prevalence of mental distress was reported (19.8%). 18 In Ethiopia, a study done among 10,203 residents of Addis Ababa using SRQ-20 revealed a prevalence of mental distress 11.7%.…”
Section: Introductionmentioning
confidence: 98%
“…16 Research from Uganda shows the level of stress among health science students was 57.4% and a study from Zimbabwe reported a Higher prevalence of mental distress (64.5%) amongst first-year medical students. 16,17 In Somaliland at the University of Hargeisa, a lower prevalence of mental distress was reported (19.8%). 18 In Ethiopia, a study done among 10,203 residents of Addis Ababa using SRQ-20 revealed a prevalence of mental distress 11.7%.…”
Section: Introductionmentioning
confidence: 98%
“…Globally, recent studies have widely reported mental disorders and suicidal behaviours among university and college students in general, with suicidal ideations and other related mental health challenges being more frequent in females and adolescents (Amanya, Nakitende, & Ngabirano, 2018;Auerbach et al, 2016;Eskin et al, 2016;Han et al, 2016;Li et al, 2014;Mortier et al, 2015Mortier et al, ,2017Okwaraji & En, 2014;Yang, Zhang, Sun, Sun, & Ye, 2015). However, studies with focus on estimating the prevalence and determining the socio-demographic factors that present as correlates, risks or protective factors related to suicidal behaviours specifically among nursing (and midwifery) students are generally inadequate.…”
mentioning
confidence: 99%
“…A descriptive cross-sectional survey conducted among undergraduate health professional students at Makerere University College of Health Sciences from the first year to the fifth year by Sharon Bright Amanya [1]…”
Section: Review Of Literaturementioning
confidence: 99%